EVALUATING CAUSES OF ROAD FAILURE ALONG KM 5, ADO-IKERE-EKITI ROAD, SOUTHWESTERN NIGERIA - Ajayi, C. A.; Abdu-Raheem, Y. A.; Talabi, A. O.; Ilugbo S.O. (Engineering Heritage Journal)
A geophysical study of the failed portion of the Ado-Ikere-Ekiti road along Km5 was conducted to investigate the causes of its failure and proffer appropriate solutions to stop the failure. Vertical Electrical Sounding (VES), 2D Electrical Resistivity Tomography (ERT), and Electromagnetic (EM) impact survey using Schlumberger, Dipole-Dipole, and Gradient arrays respectively were employed for the study. VES data were interpreted quantitatively by partial curve matching and computer-assisted forward modeling using the IPI2Win(R) software. The geo-electric parameters obtained from the VES interpretation were used to generate a geo-electric section beneath the traverse. The 2-D subsurface resistivity structures of the failed portion of the road were obtained by processing and interpreting the data obtained from the ERT quantitatively employing the inverse modeling with DIPRO for Windows software. The EM survey electromagnetic fields were transmitted into the ground at varying frequencies to generate an output of frequency effect in percentage which is interpreted as apparent resistivity. The 1D EM geo-section generated by the instrument was used to delineate different formations like clayey/weathered, partly weathered, fractured basement, and fresh basement. The VES soundings produced different geo-electric curve types including the H, K, HA, HK, and KHA types. The geo-electric section revealed four subsurface geo-electric layers including the topsoil, weathered zone, fresh basement, and fractured basement. The topsoil resistivity values ranged from 249-685 ohms-m with a thickness range of 0.6 – 12.8 m. The topsoil is made up of lateritic-sandy soil. The second layer is the weathered zone with resistivity values ranging from 52 – 230 ohms-m and thickness from 0.7- 31.2 m. The third layer is the fresh basement with resistivity values ranging from 532-2866 ohms-m. The fourth layer constitutes the fractured zone of the study area with resistivity values of 269 – 422 ohms-m. The dipole-dipole arrangement revealed a hollow structure that suggested the possibility of a buried stream channel across the study area in an East-West direction. The EM survey confirmed the findings of the electrical resistivity surveys revealing highly weathered zones and the occurrence of deep fractured bedrock even at greater depth. It further confirmed the possibility of the buried river channel in the area. This study showed the possible causes of road failure to be the presence of a thin competent lateritic layer underlain by the thick weathered zone, the presence of fractured zones beneath the weathered zone, and lack of proper drainage at the road embankment. Suggested solutions to this problem include employing stabilization methods (compaction, grouting, or chemical stabilization) for the weathered zones, rock bolting, and grouting for the fractures and putting up drainage systems at the road embankments.